Atypical Linear Tectonic Block of the Intraplate Deformation Zone in the Central Indian Ocean Basin - Vsevolod V. Yutsis; Oleg V. Levchenko; Alexander V. Tevelev; Yulia G. Marinova; Ilia A. Veklich; Abraham Del Razo Gonzalez (Journal of Marine Science and Engineering)
The Central Indian Ocean Basin (CIOB) is distinguished by unusually high tectonic activity, setting it apart from all other passive oceanic basins. Within the interior of the Indo-Australian lithospheric plate lies a unique area of intraplate deformation. This region is characterized by the highest recorded intraplate oceanic seismicity, with earthquake magnitudes reaching up to M = 8, abnormally high heat flow—measured to be two to four times higher than background levels for the ancient oceanic lithosphere of the Cretaceous age—and, most notably, intense folding and faulting of sediments and the basement, which are typically associated only with boundary zones of lithospheric plates. This anomalously tectonically active intraplate area was studied during regular research cruises in the 1970s–1980s, after which new conclusions were mainly drawn from satellite data modeling. Substantially new geophysical data were obtained in 2017 after a long gap. Bathymetric surveys using multibeam echosounders during the 42nd cruise of the R/V (Research Vessel) Akademik Boris Petrov and the SO258/2 cruise of the R/V Sonne provided full coverage of a large portion of the intraplate deformation area in the CIOB. This confirmed the mosaic-block structure of the intraplate deformation zone in the Central Indian Ocean Basin, consisting of numerous isometrically deformed tectonic blocks. A linear block at 0.2–0.6° S, which has a branch-like shape in plain view, is morphologically distinct from these blocks. It represents a system of structural elements of different scales (folds, flexures, ruptures), which constitute a structural paragenesis formed in the mechanical environment of a dextral transpressive tectonic setting.